Pragmatisme dalam Perdagangan Ilegal Satwa Liar: Analisis Teori Philosophy of Money George Simmel - Bilbina Iqlima Putri; Nashriyah Ummuhany; Azkia Nur Shadrina Hayati; Fitriyani Fitriyani; Alifvia Ridzky Hidayanti; Didi Pramono (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to find out the causes of wildlife trade, the factors that drive the continued of illegal trade and the consequences which is studied in the perspective of Georg Simmel's philosophy of money theory. The method used is descriptive qualitative derived from the analysis of one of the videos in the watchdoc youtube channel and literature review from several sources of national and international articles. The results showed that the existence of wildlife trade in animal markets is a form of weak law enforcement and the lack of prosperity of Indonesian which also affects on other living creatures. The main factor behind the wildlife trade is economic. Economic difficulties force some people to do various ways to survive, one of which is by buying and selling wildlife that is considered to be quite profitable. However, the impact of this wildlife trade is also a concern because it can lead to zoonosis that threatens human health. This illegal trade is a manifestation of Georg Simmel's theory that money moves in the social, money adjusts itself in social relations, and how money affects social phenomena that happens in society. The effort that can be made to decrease the rampant wildlife trade is by consciously enforcing the applicable regulations together.